Industrial training report: Industrial training report: Perpustakaan Sultanah Nur Zahirah, Universiti Malaysia Terangganu / Nurul Syahida Zakari @ Awang - Zakari @ Awang, Nurul Syahida (Faculty of Information Management, 2018)
The purpose of this documentation is to report the activities undergone by the trainee during the Industrial Training for five months in Perpustakaan Sultanah Nur Zahirah (PSNZ). The report includes daily task that assigned to the students practical such as cataloging, circulation, digitization, manage equipment and also manage the activities. Moreover, the most vital part is where the student’s practical has been assigned with a special project which is to provide a QR codes projects. The objective of this volunteering project is to encourage reading culture parallel with mandate Education Minister Dr Mazlee Malik that aimed at forming a world class knowledge society. The purpose of this project is easier the reader to read anything educational.